2013
DOI: 10.2478/johh-2013-0015
|View full text |Cite
|
Sign up to set email alerts
|

The combined use of wavelet transform and black box models in reservoir inflow modeling

Abstract: In the study presented, different hybrid model approaches are proposed for reservoir inflow modeling from the meteorological data (monthly precipitation, one-month-ahead precipitation and monthly mean temperature data) by the combined use of discrete wavelet transform (DWT) and different black box techniques. Multiple linear regression (MLR), feed forward neural networks (FFNN) and least square support vector machines (LSSVM) were considered as the black box methods. In the modeling strategy, meteorological in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Hemmati-Sarapardeh et al (2014) determined the reservoir oil viscosity using LSSVR approach. However, there are limited studies in the literature related to application of LSSVR in water resources (Guo et al 2011;Hwang et al 2012;Kisi 2012Kisi , 2013Okkan and Serbes 2013). Guo et al (2011) used LSSVR for prediction of reference evapotranspiration and found promising results.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Hemmati-Sarapardeh et al (2014) determined the reservoir oil viscosity using LSSVR approach. However, there are limited studies in the literature related to application of LSSVR in water resources (Guo et al 2011;Hwang et al 2012;Kisi 2012Kisi , 2013Okkan and Serbes 2013). Guo et al (2011) used LSSVR for prediction of reference evapotranspiration and found promising results.…”
mentioning
confidence: 96%
“…He showed that LSSVR model performed better than the NN and other models. Okkan and Serbes (2013) used and proposed LSSVR with wavelet in reservoir inflow modeling. Despite the reported success of employing LSSVR in numerous studies, to the best of our knowledge the capability of LSSVR has not yet been examined in terms of streamflow forecasting.…”
mentioning
confidence: 99%
“…With the impetus to predict the depths of groundwater in 64 wells dug in the Munijhara micro-basin at Orissa, Similarly, several researchers have used ANN to predict groundwater levels in confined aquifers [13; 14], in leaking aquifers [15; 16] and in multi-layer aquifers. In recent years, the conjunction of wavelet transformation and ANN techniques has been successfully implemented in hydrological applications [18][19][20][21][22][23][24]. The wavelet transform is another technique which can analyze a signal in time and frequency in order to overcome the disadvantages of the conventional Fourier transform.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, hybrid time series modeling approaches utilizing wavelet transform have been one of the research themes studied actively in the hydrological field [8][9][10][11][12][13][14]. In terms of signal analysis, the wavelet transform is a signal decomposition method which splits an original signal into sub-signals, including detail and approximation (smooth) components.…”
Section: Introductionmentioning
confidence: 99%
“…Kisi et al [11] predicted short-and long-term air temperatures using wavelet-based genetic programming. Okkan and Serbes [12] modeled reservoir inflow using a combination of DWT and black box models including ANNs, multiple linear regression and least square support vector machines (LS-SVMs). …”
Section: Introductionmentioning
confidence: 99%